2002
DOI: 10.1046/j.1365-2133.2002.04952.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized heat urticaria in a patient is associated with a wealing response to heated autologous serum

Abstract: We report a case of localized heat urticaria in a 71-year-old woman who developed weals and loss of consciousness after taking a bath. Exposing her skin to heat at 40 degrees C or immersing her hands in water at 40 degrees C produced urticarial lesions and increased her plasma histamine level. Desensitization with hot water improved her symptoms and normalized her plasma histamine level after heat challenge. An intracutaneous injection of her serum produced no reaction, while an injection of her serum that had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
(22 reference statements)
2
14
0
1
Order By: Relevance
“…demonstrated that heat‐decomplemented or IgG‐depleted serum of patients with CU was unable to induce basophil degranulation in vitro , but retained the ability to induce weal and flare reactions in vivo . A weal and flare skin reaction to ASST was observed in a patient with LHU when her serum was heated to 40 and 60 °C for 15 and 30 min, respectively, then injected at RT . Similarly in our patient, ASST gave a positive response, but only when serum previously heated to 56 °C for 30 min (conditions for IgE denaturation and permanent complement inactivation) was used.…”
Section: Reportsupporting
confidence: 66%
See 1 more Smart Citation
“…demonstrated that heat‐decomplemented or IgG‐depleted serum of patients with CU was unable to induce basophil degranulation in vitro , but retained the ability to induce weal and flare reactions in vivo . A weal and flare skin reaction to ASST was observed in a patient with LHU when her serum was heated to 40 and 60 °C for 15 and 30 min, respectively, then injected at RT . Similarly in our patient, ASST gave a positive response, but only when serum previously heated to 56 °C for 30 min (conditions for IgE denaturation and permanent complement inactivation) was used.…”
Section: Reportsupporting
confidence: 66%
“…Autologous venous blood (5 mL) was kept at room temperature (RT) for 30 min, then serum and plasma were extracted by standard centrifugation and divided into aliquots. Some of the aliquots were kept at RT, while some were partially heated to 40 or 45 °C for 15 min (as described in previous papers about LHU) or to 56 °C for 30 min (to obtain complement inactivation), before being cooled back down to RT. We then injected 0.05 mL of sterile 0.9% saline solution (as negative control), histamine phosphate 10 μg/mL (as positive control), serum (preheated or not) and plasma (preheated or not) intradermally into the patient's volar forearm.…”
Section: Reportmentioning
confidence: 99%
“…In einer Untersuchung wurde bei einem Patienten mit lokalisierter Wärme-urtikaria eine positive Reaktion beim Intrakutantest mit erhitztem autologen Serum, aber nicht nach Injektion des unbehandelten Serums festgestellt.Weitere Untersuchungen ließen vermuten, dass der Auslöser ein wärmeverändertes,aber hitzestabiles Protein ist [5].…”
Section: Wärmeurtikariaunclassified
“…It was experienced that performing several procedures on patient’s serum may enhance the ASST results. While ASST was negative in a patient with heat urticaria, the second ASST performed with heated serum resulted in a positive reaction 2 . In addition, the ASST result of a patient with solar urticaria turned to positive when performed after exposing serum to visible light, as well 3 .…”
Section: Discussionmentioning
confidence: 97%
“…It does not prove the presence of antibodies, it rather shows histamine‐releasing properties of the tested serum 1 . It was observed that while the ASST result was negative in a patient with localized heat urticaria, the result turned to positive when ASST was performed with heated serum, indicating that the patient’s serum may have contained some urticaria‐inducing factors that can be modified by heat 2 . Additionally, visible light‐irradiated serum induced a positive reaction in an ASST‐negative (ASST−) solar urticaria patient, which was inhibited with exposition of inhibition spectrum light 3 .…”
Section: Introductionmentioning
confidence: 99%